Arm Propulsion in Front Crawl Stroke - Cristian Romagnoli; Vincenzo Bonaiuto; Giorgio Gatta (Sports)
Objectives: This study aims to determine the propulsive force and effective arm area contributed by the propulsion through the dynamic balance (power balance) between drag and propulsive power in swimming crawl performance. Methods: Ten male swimmers participated in the study. The athletes conducted the crawl trials at a constant velocity using only the upper limbs. Data were collected using a Spectro instrument to measure the drag and 3D video analysis for kinematic of upper limbs movement. Results: The power balance was confirmed through the Bland–Altman estimation (estimated bias 8.5) and was also demonstrated by a one-way analysis of variance that does not show statistical differences. Subsequently, by applying the power balance, the effective propulsive area could be estimated. The result shows an increase of ~8.5% over the value at the hand area used to verify the power balance. This value appears to be attributable to a percentage of the forearm area to propulsive action. Conclusions: This information will allow athletes and coaches to constantly monitor the propulsive force and power, providing useful data on arm movement and swimming technique. Indeed, deeper knowledge about the athlete’s swimming technique can reduce the possibility of suffering micro-traumas in the elbows and shoulders.